Simultaneous extraction and preliminary purification of polyphenols from grape pomace using an aqueous two-phase system exposed to ultrasound irradiation: Process characterization and simulation - Xie, Guangjie; Shen, Juan; Luo, Ji; Li, Dandan; Tao, Yang; Song, Changnian; Han, Yongbin (Frontiers in Nutrition, 2022)
In this study, an ultrasound-assisted aqueous two-phase (ATP) extraction method was used for the extraction and purification of phenolic compounds from grape pomace. The effect of acoustic energy densities (AED, 41.1, 63.5, 96.1, 111.2 W/L) and temperatures (20, 30, 40°C) on the yield of phenolics was investigated. An artificial neural network (ANN) was successfully used to correlate the extraction parameters with phenolic yield. Then, a diffusion model based on Fick's second law was used to model the mass transfer process during ultrasound-assisted ATP extraction and evaluate the effective diffusion coefficient of phenolics. The results revealed the increase in AED, and the temperature increased the effective diffusivity of phenolics. The HPLC analysis of anthocyanins and flavonols showed that ultrasound significantly increased the extraction yield of anthocyanins compared with the traditional method. High amounts of rutin and myricetin were recovered using the ATPS systems. Sugars were mainly distributed in the bottom phase, whereas phenolics were located in the top phase. Conclusively, ultrasound-assisted aqueous two-phase (ATP) extraction can be used as an effective method to achieve the simultaneous separation and preliminary purification of phenolics from grape pomace.